2017
DOI: 10.1016/s2468-1253(17)30056-0
|View full text |Cite
|
Sign up to set email alerts
|

Autologous stem-cell transplantation in treatment-refractory Crohn's disease: an analysis of pooled data from the ASTIC trial

Abstract: BACKGROUND The randomised controlled ASTIC trial showed no benefit of mobilisation and autologous haematopoietic stem-cell transplantation (HSCT) compared with mobilisation followed by conventional therapy using a stringent primary endpoint (steroid-free clinical remission for 3 months with no endoscopic or radiological evidence of intestinal inflammation) in patients with treatment-refractory Crohn's disease. We now assess HSCT in patients enrolled in the ASTIC trial using endpoints that are traditional for c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
70
0
2

Year Published

2017
2017
2019
2019

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(73 citation statements)
references
References 29 publications
1
70
0
2
Order By: Relevance
“…The primary outcomes in ASTIC have been criticized for being too stringent. A further 1 year follow up study, including pooled data from ASTIC, showed clinical benefit in 40 transplant patients [106]. Evidence of efficacy with complete endoscopic healing in 50% of patients, and 47% were assessed as free of disease on endoscopy and radiology imaging at 1 year.…”
Section: Autologous Haematopoietic Stem Cell Therapymentioning
confidence: 98%
See 1 more Smart Citation
“…The primary outcomes in ASTIC have been criticized for being too stringent. A further 1 year follow up study, including pooled data from ASTIC, showed clinical benefit in 40 transplant patients [106]. Evidence of efficacy with complete endoscopic healing in 50% of patients, and 47% were assessed as free of disease on endoscopy and radiology imaging at 1 year.…”
Section: Autologous Haematopoietic Stem Cell Therapymentioning
confidence: 98%
“…Of the 23 patients with available data 76 serious adverse events occurred, most commonly treatment related infection. Smoking and per-anal disease were associated with increased serious adverse events [106].…”
Section: Autologous Haematopoietic Stem Cell Therapymentioning
confidence: 99%
“…Dennoch gibt es weiterhin therapierefraktäre Krankheitsverläufe mit hoher Einschränkung der Lebensqualität. Eine randomisierte und kontrollierte Studie zur HSCT liegt vor, konnte aber auf den ersten Blick keine Überlegenheit der HSCT gegenüber der Standardtherapie zeigen [16]. Bei genauerer Betrachtung und insbesondere unter Hinzunahme der Patienten, welche als Rescue-Therapie dann doch noch einer HSCT zugeführt wurden, konnte bei 50 % der Therapierten eine endoskopisch und bioptisch gesicherte komplette Abheilung der Mukosa beobachtet werden [17].…”
Section: Morbus Crohnunclassified
“…MSCT has been evaluated for the treatment of IBD in two different modalities; intralesional injection to treat fistulas in CD, and intravenous administration to treat luminal CD and UC. Local injection of autologous and allogeneic MSCs have shown positive results in multiple case series and randomized controlled trials compared to placebo in patients with complicated fistulizing disease, not responding to traditional therapies with immunomodulators, anti-TNF alpha agents, and local management, including surgery (23,24). A 12-patient, 6-month, phase 1 trial has shown an 83% rate of complete clinical healing and radiological evidence of response of complicated fistulas in CD patients treated with intrafistulous autologous MSCT (25).…”
Section: Mesenchymal Stem Cell Transplant (Msct) In Ibdmentioning
confidence: 99%